THE ROLE OF HEALTH WORKERS IN PROVIDING PRE SECTIO CAESAREAN CARE FOR MATERNITY MOTHERS AT GRIYA HOSPITAL MEDICA BATAM IN 2024 - Elisa Angelina Tambunan; Rosmani Sinaga; Intan Nur Indah Sari; Juliana Munthe; Nova Marianti Purba; Natasya Sulistiawati; Sri Elvi Yesya (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Caesarean section is one of the most popular types of childbirth after a normal delivery. According to the WHO, the recommended standard of caesarean section in many countries is about 10–15% of total births. A 2021 WHO report revealed that caesarean section has become an increasingly common option, with a proportion reaching 21% of total deliveries globally. Basic Health Research data shows that SC surgeries account for 15.3% of the total surgical practices in all provinces in Indonesia. A survey conducted on mothers who gave birth in the last 5 years in 33 provinces revealed that in Central Java, SC surgery is the birth option for 77% of maternal mothers. The proportion of SC deliveries in Government Hospitals in Indonesia reaches around 20–25% of the total number of deliveries. Data shows that private hospitals have a higher percentage of SC deliveries, ranging from 30–80% of the total number of deliveries. The high rate of SC childbirth in Indonesia is caused by several factors, such as the SC childbirth process is suspected to be more not due to medical indications, but from patient demand. Method: This research method is observational/survey using questionnaires or questionnaires without intervention. The type of research is descriptive analytics with cross-sectional. Conclusion: The majority of health workers with bachelor’s and master’s/professional education are 16 people (46%) each and the minority of diploma education is 3 people (9%). The majority of health workers aged approximately 35 years are 22 people (63%) and the minority over 35 years old is 13 people (37%). The majority of health workers have worked for less than 1 year (80%) and minorities with less than 1 year of work are 7 people (20%). The majority of training history was approximately 1 time as many as 20 people (57%) and the minority of training history was 15 people (43%). Health workers with good knowledge as many as 25 people (71%) and minority knowledge as many as 3 people (9%). The majority of positive attitudes were 20 people (57%) and the minority of negative attitudes were 15 people (43%). The majority of skilled health workers are 25 people (71%) and the minority is unskilled as many as 10 people (29%).